Detection of Lumpy Skin Disease Virus in Transhipped Through Merak Port and The Impact of its Spread - Rafiq, Faizal; Murtini, Sri; -, Mujiatun; -, Helmi; Raditya, Mochammad Nova (Jurnal Sain Veteriner, 2024)
Research to detect the presence of Lumpy Skin Disease Virus (LSDV) was carried out in the work area of the Banten Animal, Fish and Plant Quarantine Center (BBKHIT). Sampling for LSDV detection was taken from cattle that were being transported both in and out of Merak Port. The aim of this research is to detect the presence of LSDV both clinically and in laboratory examinations at Merak Port and estimate the impact of its spread. 152 mouth and nose swab samples were taken, then a quantitative real time PCR (qPCR) test was carried out. The results of the study showed that there were no clinical symptoms observed in the trafficked cattle, however there were 2 positive samples for LSD by molecular testing using qPCR. These results can be said to be subclinically infected cattle. Positive samples came from cattle trafficked from Sumbawa Regency and Central Lampung Regency with respective Ct values of 27.71 and 28.88. Estimates of the impact of the spread of LSDV were carried out based on the categories of breeding cattle and beef cattle. The impact of the spread of LSDV is estimated to be more dangerous and will occur in breeding cattle because of their long lifespan during the rearing process. This means that the LSD virus can continue to spread to other cows rather than cows that are immediately slaughtered.